Early resonances of Tethys and Dione: Implications for Ithaca Chasma - Hussmann, Hauke; Rodríguez, Adrián; Callegari, Nelson [UNESP]; Shoji, Daigo (Elsevier, 2019)
We investigate the tidal evolution of Tethys identifying several possible resonance scenarios that could be relevant for intense tidal heating and the formation of Ithaca Chasma early in the satellite's history. By studying the phase-space we identify initial conditions for which Tethys and Dione can be trapped in a 2:1 mean motion resonance. From evolution models we show that capture of Tethys in this resonance is indeed possible. This scenario would imply a small semi-major axis of Tethys early in its history and small Q-values (high dissipation rates) of Saturn. Various resonance scenarios are obtained including later evolution out of resonance. As a result of the early 2:1 resonance tidal heating can be significantly enhanced in Tethys. Depending on the assumed dissipation factor of Saturn at the time of the resonance, the resulting global dissipation rate ranges between 20 and several hundred GW and could provide the heat pulse associated with the formation of Ithaca Chasma, a global rift system on Tethys. In addition, the orbital expansion due to tides will lead to surface stresses that could trigger the formation of Ithaca Chasma. The stress pattern is consistent with the orientation of faults of Ithaca Chasma at high latitudes but the orientation does not match for the equatorial regions. Expansion due to freezing of an early subsurface ocean as suggested in previous studies could be an additional factor required to explain the formation and orientation of the rift system at low latitudes.
Keywords: Ithaca Chasma; Resonances; Tethys